History of Muammar Qaddafi’s Political Pragmatism: His Thought of Arab Unity and Israel – Palestine Matter - Pratama, Fikri Surya (Al-Isnad: Journal of Islamic Civilization History and Humanities, 2024)
Qaddafi's political policies in the Middle East were closely tied to the Israeli-Palestinian conflict. This article aims to explore Qaddafi's political ideology regarding Arab unity, support for Palestine, and condemnation of Israel and Zionism. The research conducted for this article is qualitative, using an analytical and descriptive approach to character study. The political history approach is used to understand Qaddafi's political thought. The research results indicate that Qaddafi employed the Israeli card to strengthen his position as a revolutionary leader in the Arab world and as a defender of the Palestinian people. He also used it to compete with the leaders of Syria and Egypt, whom he considered political rivals. Despite having close trade ties with Israel, he stated that this did not affect his political vision. From Qaddafi's perspective, recognizing the legitimacy of the Jewish state would betray one of the fundamental principles of the revolution he had championed.